Validity of Rapid Diagnostic Test for Malaria Screening at Puskesmas Harapan Jayapura Regency - Zusana Lena Tulak (MIRACLE Journal Of Public Health, 2021)
Malaria is an infectious disease caused by five types of Plasmodium and can cause death. Type of plasmodium that is infecting a malaria patient, should be diagnosis exactly in order to treat it properly, and can avoid death. This Malaria RDT iin Sentani Jayapura Regency, Papua Province, which is used in diagnosing malaria in the area. The aims of this study is to determine the specificity and sensitivity of the malaria RDT that used at the Harapan Public Health Center in Jayapura Regency compared to the gold standard (microscopic). This study is an survey descriptive study that describes factually the quality of the used RDT. The tools and materials used were the malaria RDT, slides, microscopes and other supporting materials for malaria microscopic examination. The sample used was finger blood from public health care visitors who had clinical symptoms of malaria. The test results showed that of the 19 samples examined there were 4 true positive samples (RDT and microscopic), and 13 true negative samples (RDT and microscopic), and 2 samples read invalid on RDT, but on microscopic examination it read negative. From the results of these readings, the sensitivity and specificity values ​​were obtained at 100%. The conclusion of this activity is that RDT is still effective as a malaria diagnostic tool that can detect it quickly and accurately, especially in high endemic areas such as Papua.